Effect of ice maturation, freezing and heat treatment on the peelability and quality of cold water shrimps (Pandalus borealis). (December 2020) - Gringer, Nina; Skytte, Jacob Lercke; Dang, Tem Thi; Orlien, Vibeke; Olsen, Karsten; Schlippè-Steffensen, Kaino; Jessen, Flemming
Abstract: Steamed (90 s) cold water shrimps ( Pandalus borealis ) were analysed for the effect of ice maturation (1–4 days) before steaming, frozen storage (2 months at −20 °C) and catching locations (2 batches) with respect to changes in texture, colour and peelability. In addition, the interdependency of the attributes of uncooked and steamed shrimps were assessed by analysing 1760 shrimps in total. Results showed that the longer maturation time the springier and more yellow the ready-to-eat shrimps got. Besides, frozen storage prior to ice maturation and steaming led to springier, chewier and harder shrimps compared to the unfrozen product. Frozen storage also induced increased yellowness, which negatively affected the quality of the shrimps. The expected positive effect of maturation time on peelability could not be confirmed by the mechanical peeling work measurements. Studying the interdependency of steamed and uncooked shrimps showed that the steaming process increased the springiness and decreased the hardness, resilience and chewiness of the shrimps as maturation took place. Furthermore, the steaming resulted in more white shrimps, which were slightly easier to peel. In conclusion, maturation time, freezing and steaming all affected the quality of the ready-to-eat shrimps, whereas the peeling work was not affected. Highlights: Quality (colour and texture) of steamed shrimps changed with maturation time on ice. The longer maturation time the springier the steamed shrimps got. The steamed shrimps became more and more yellow with maturation time. Frozen storage of shrimps prior to ice maturation affected the colour negatively. Frozen storage resulted in an increase of springiness, chewiness and hardness.